2020
DOI: 10.3390/f11050513
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Responses of Two Subtropical Tree Species (Schima superba and Cunninghamia lanceolata) to Heat Waves

Abstract: The frequency and intensity of heat waves (HWs) has increased in subtropical regions in recent years. The mechanism underlying the HW response of subtropical trees remains unclear. In this study, we conducted an experiment with broad-leaved Schima superba (S. superba) and coniferous Cunninghamia lanceolata (C. lanceolata) seedlings to examine HW (5-day long) effects on stem water transport, leaf water use efficiency (WUE), morphology and growth, and to elucidate differences in the responses of both species. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…There are different ways plants demonstrate adaptative differentiation of thermal tolerance , such as differences in structural tissues, proteins, and physiology (Aspinwall et al ., 2019; Maher et al ., 2019). While there are substantial gaps in knowledge in our understanding of plant thermal tolerance (Geange et al ., 2020), common garden experiments controlling for environment have confirmed that traits providing tolerance to heatwaves are genetically determined across species (Ruthrof et al ., 2018; Aspinwall et al ., 2019; Qu et al ., 2020). Among examples of inter‐specific genotypic differentiation is a global study measuring 218 species across seven biomes, which found that thermal tolerance (measured as the maximum temperature for PSII) was highly variable among co‐occurring species (O’Sullivan et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways plants demonstrate adaptative differentiation of thermal tolerance , such as differences in structural tissues, proteins, and physiology (Aspinwall et al ., 2019; Maher et al ., 2019). While there are substantial gaps in knowledge in our understanding of plant thermal tolerance (Geange et al ., 2020), common garden experiments controlling for environment have confirmed that traits providing tolerance to heatwaves are genetically determined across species (Ruthrof et al ., 2018; Aspinwall et al ., 2019; Qu et al ., 2020). Among examples of inter‐specific genotypic differentiation is a global study measuring 218 species across seven biomes, which found that thermal tolerance (measured as the maximum temperature for PSII) was highly variable among co‐occurring species (O’Sullivan et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be due to the dropping water potential and increasing embolization in branches under high temperatures and transpiration during the hottest months [40]. Consequently, this may result in insufficient water supply, decreased stomata conductance of leaves [52][53][54], and even loss of photosynthetic tissue [55]. Further, this may result in a reduction in photosynthetic production and carbon reserves in the late growing season, with negative effects on radial growth in the current and following years [56,57].…”
Section: The Negative Effect Of High Temperatures In the Late Rainy S...mentioning
confidence: 99%